The biomechanical and histological effects of posterior cruciate ligament rupture on the medial tibial plateau - Deng, Zhenhan (J Orthop Surg Res, 2017)
BACKGROUND: The objective of this study was to investigate the biomechanical and histological effects of the posterior cruciate ligament (PCL) on the medial tibial plateau. METHODS: A total of 12 cadaveric human knee specimens were collected and grouped as follows: the PCL intact group (n = 12), the anterolateral bundle rupture group (n = 6), the postmedial bundle rupture group (n = 6), and the PCL rupture group (n = 12). The strain on the anterior, middle, and posterior parts of the medial tibial plateau with an axial loading force at different flexion angles was measured and analyzed, respectively. Forty-eight rabbits were chosen for animal study: surgery was performed on the one side of each rabbit randomly (experimental group), while the other side was taken as control (control group). Every 12 rabbits were culled at each of the four selected time points to collect the medial tibial plateau for morphological and histological observation. RESULTS: The PCL rupture, either partial or complete, may generate an abnormal load on all the parts of the medial tibial plateau with axial loading at all positions. Noticeable time-dependent degenerative histological changes of the medial tibial plateau were observed in the rabbit models of PCL rupture. Compared with the control group, all the PCL rupture groups exhibited a higher expression of the matrix metalloproteinase-7 (MMP-7) and the tissue inhibitors of metalloproteinase-1 (TIMP-1) at all the time points. CONCLUSIONS: Either partial or complete PCL rupture may generate an abnormal load on all the parts of the medial tibial plateau with axial loading at all the positions and may cause cartilage degeneration on the medial tibial plateau.